2010
DOI: 10.5194/acp-10-3875-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative humidity on aerosol light scattering in the Arctic

Abstract: Abstract. Aerosol particles experience hygroscopic growth in the ambient atmosphere. Their optical properties -especially the aerosol light scattering -are therefore strongly dependent on the ambient relative humidity (RH). In-situ light scattering measurements of long-term observations are usually performed under dry conditions (RH<30-40%). The knowledge of this RH effect is of eminent importance for climate forcing calculations or for the comparison of remote sensing with in-situ measurements. This study com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(179 citation statements)
references
References 35 publications
14
151
4
Order By: Relevance
“…The similarity results from the low scattering enhancement factor (e.g., f (80 %) = 1.44 ± 0.12) at Lin'an, which was similar to the value (f (80 %) = 1.33 ± 0.07) obtained by Gassó et al (2000) for a dust event. The f (RH) in other studies was much higher than that at Lin'an, ranging from 2.04 (polluted marine aerosols in Gassó et al, 2000) to 3.77 (arctic aerosols in Zieger et al, 2010), and therefore their parameter g was much higher.…”
Section: Parameterization With Equationmentioning
confidence: 87%
See 3 more Smart Citations
“…The similarity results from the low scattering enhancement factor (e.g., f (80 %) = 1.44 ± 0.12) at Lin'an, which was similar to the value (f (80 %) = 1.33 ± 0.07) obtained by Gassó et al (2000) for a dust event. The f (RH) in other studies was much higher than that at Lin'an, ranging from 2.04 (polluted marine aerosols in Gassó et al, 2000) to 3.77 (arctic aerosols in Zieger et al, 2010), and therefore their parameter g was much higher.…”
Section: Parameterization With Equationmentioning
confidence: 87%
“…The wavelength dependence of scattering enhancement factor f (RH,λ) varies with generalized aerosol types. Kotchenruther and Hobbs (1998) and Zieger et al (2010Zieger et al ( , 2011 found no pronounced wavelength dependence of f (RH,λ) for biomass burning aerosols and arctic aerosols, respectively; Zieger et al (2013) found small variations (< 5 %) of f (RH,λ) at 450, 550, and 700 nm for several European sites; Kotchenruther et al (1999) and Magi and Hobbs (2003) reported significant wavelength dependence of f (RH,λ) for urban/industrial aerosols off the east coast of the United States. In this study, the wavelength dependence of enhancement factors was also investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous experimental and modeling studies have investigated the influence of RH on optical properties of aerosol particles, which is often described with the enhancement factor f (RH), defined as the ratio of aerosol scattering coefficient at a given RH and the scattering coefficient at dry conditions (see e.g., Zieger et al, 2010). f (RH) has been investigated in a number of studies at various locations (see Table 1), typically by comparing the signal of a nephelometer operated at a given RH to a corresponding instrument at dry conditions.…”
Section: Introductionmentioning
confidence: 99%